(untitled) (American Journal of Islam and Society, 1992)
The theme of the Fourth International Islamic Economics Seminar was "Economic Growth and Human Resource Development in an Islamic Perspective." It was a joint undertaking of the Association of Muslim Social Scientists (AMSS) and the International Institute of Islamic Thought (IIIT). The program was divided into five sessions: a) Human Resource Development in an Islamic Perspective; b) Human Resource Development in a Comparative Perspective; c) Issues in Human Resource Development: Case Studies from Selected Muslim Countries; d) Human Resources, Economic Development, and Government Policies in Muslim Countries; and e) Business Sector and Human Resource Development. This latter session also dealt with the role of financial institutions in human development from an Islamic perspective. Welcoming and opening remarks were made by Sultan Ahmad of the World Bank and Sayyid Syeed of the AMSS ...